Analyze the Efficacy of Silymarin in Treating Newly Diagnosed Cases of Type 2 Diabetes Mellitus by Contrasting its Effects on Glycemic Control and Insulin Resistance - Salman Khan, Muhammad Salman, Ijaz Ali, Najma Fatima, Maryam Mastoor, Tahir Mukhtar Sayed, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this research was to examine the efficacy of Silymarin in treating newly diagnosed cases of type II diabetes mellitus (T2DM), specifically with regard to glycemic control and insulin resistance. Study design: An observational, randomized, placebo- controlled study. Place and duration: Medicine department of Dr. Akbar Niazi Teaching Hospital (ANTH), Islamabad for the duration from August 2021 to January 2022. Methods: The sixty individuals with a recent diagnosis of type 2 diabetes were chosen at random. There were a total of 60 patients, split evenly between 2 groups of 30. For 90 days, those in Group A took a silymarin capsule containing 200 mg, whereas those in Group B had a placebo capsule looking very similar to the real thing. Fasting blood glucose (FBG), random blood glucose (RBG), glycated haemoglobin A1C (A1C), fasting insulin (FI), and homeostasis model assessment of insulin resistance (HOMA-IR) were measured before and after therapy. The data was examined after 90 days. Statistical analysis was performed using SPSS-20.0. If the probability value was less than 0.05, it was considered significant. The Chi-squared test was employed for statistical analysis. Results: Mean age of the patients of group A (silymarin) was 50.5 years while mean age of group B (controlled) patients was 51.0 years. In both the groups, females were more in numbers as 80% in silymarin group and 70% in controlled group. There was no significant difference showed on the basis of age, gender, BMI, education, family history and employment. Silymarin therapy for 12weeks improved the levels of RBG, RBG, HbA1c, FSI and HOMA-IR. A significant difference p-value<0.001 was showed in these variables between the two groups at baseline and after 90days treatment. Conclusion: The treatment of Silymarin supplementation of 200mg three time a day for newly diagnosed type II diabetic patients had a beneficial effect on improving the blood glucose levels and decreased insulin resistance as compared to standard treatment alone.